Allergen extract‐ and component‐based diagnostics in children of the ALLIANCE asthma cohort. Issue 10 (26th June 2021) - Skevaki, Chrysanthi; Tafo, Pavel; Eiringhaus, Kathrin; Timmesfeld, Nina; Weckmann, Markus; Happle, Christine; Nelson, Philipp P.; Maison, Nicole; Schaub, Bianca; Ricklefs, Isabell; Fuchs, Oliver; von Mutius, Erika; et al.
Abstract: Background: Current in vitro allergen‐specific IgE (sIgE) detection assays measure IgE against allergen extracts or molecules in a single‐ or multiplex approach. Direct comparisons of the performance of such assays among young children with common presentations of allergic diseases regardless of sensitization status are largely missing. Objectives: The aim of this study was a comparison of the analytical and diagnostic performance for common clinical questions of three commonly used technologies which rely upon different laboratory methodologies among children of the All Age Asthma (ALLIANCE) cohort (clinicaltrials.gov: NCT02496468). Methods: Sera from 106 paediatric study participants (mean age 4 years) were assessed for the presence of sIgE by means of the ImmunoCAP™ sx1 and fx5 mixes, the ImmunoCAP ISAC™ 112 microarray and a Euroline™ panel. Results: Total and negative concordance was high (>82%–>89%), while positive concordance varied considerably (0%–100%) but was also >50% for the most common sensitizations analysed (house dust mite and birch). All three test systems showed good sensitivity and specificity (AUC consistently > 0.7). However, no significant differences with regard to identifying sIgE sensitizations associated with symptoms in children with suspected pollen‐ or dust‐triggered wheeze or presenting with symptoms of allergic rhinoconjunctivitis or food allergy were detected. Extending the number of allergens did not change the similar performance of the three assay systems. Conclusion and Clinical Relevance: Among young children, the three sIgE assays showed good analytical and diagnostic concordance. Our results caution that the identification of larger numbers of sensitizations by more comprehensive multiplex approaches may not improve the clinical utility of sIgE testing in this age group. Abstract : Among 106 young children (mean age 4 years) of the All Age Asthma (ALLIANCE) cohort, ImmunoCAP™ sx1 and fx1 mixes, the ImmunoCAP ISAC™ 112 microarray, and a Euroline™ panel showed good analytical and diagnostic concordance in four common clinical scenarios. Our results caution that the identification of larger numbers of sensitizations by more comprehensive multiplex approaches may not improve clinical utility of sIgE testing in this age group.